1985
DOI: 10.1021/ma00147a011
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional aromatic crystals in solution. 4. Ground- and excited-state interactions of poly(L-1-pyrenylalanine) studied by chiroptical spectroscopy including circularly polarized fluorescence and fluorescence-detected circular dichroism

Abstract: A novel aromatic poly(a-amino acid), poly(l-1-pyrenylalanine), was synthesized in the form of a block copolymer with poly(7-benzyl DL-glutamate) as a solubilizing unit. The polymer solution in trimethyl phosphate and dimethylformamide was subjected to spectroscopic measurements including such chiroptical methods as circular dichroism (CD), circularly polarized fluorescence (CPF), and fluorescence-detected circular dichroism (FDCD). A significant hypochromicity in the absorption spectrum and strong CD Cotton ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…This group has synthesized and studied polymers in which the phenyl group of poly(Phe) is replaced by naphthyl (Sisido et al, 1983a,b) and pyrenyl (Egusa et al, 1985) groups. Molecular mechanics calculations of conformer energies and matrix method (Bayley et al, 1969) calculations of rotational strengths have given reasonable agreement with the experimentally determined CD spectra (Sisido et al, 1983a,b;Sisido and Imanishi, 1985).…”
Section: B Homopolymers Of Aromatic Amino Acidsmentioning
confidence: 99%
“…This group has synthesized and studied polymers in which the phenyl group of poly(Phe) is replaced by naphthyl (Sisido et al, 1983a,b) and pyrenyl (Egusa et al, 1985) groups. Molecular mechanics calculations of conformer energies and matrix method (Bayley et al, 1969) calculations of rotational strengths have given reasonable agreement with the experimentally determined CD spectra (Sisido et al, 1983a,b;Sisido and Imanishi, 1985).…”
Section: B Homopolymers Of Aromatic Amino Acidsmentioning
confidence: 99%
“…4, exhibit an intense negative maximum around 202 -205 nm, typical of peptides attaining a right-handed 3 10 -helical conformation [29] [30]. In the 230 -250-nm range some differences among the three peptides can be noted, probably due to an induced CD resulting from electronic transitions of the aromatic side chains (pyrene and azulene), caused by the nearest-neighbor peptide groups [31] [32].…”
mentioning
confidence: 98%
“…It has been observed that the intensity of the excimer emission in pyrene-labelled polypeptides is dependent on the chirality of the 1-pyrenylalanine employed in their synthesis [23]. Circular polarized fluorescence spectra (CPF), of pyrene-labelled polypeptides, show negative and positive dissymmetries in the pyrene excimer emission wavelength range [24].…”
Section: Discussionmentioning
confidence: 99%
“…Dissymmetric CPF spectra are diagnostic of the presence of the more than one emissive species [25]. Egusa et al [23,26] attributed the dissymmetry observed in the CPF spectra of pyrenelabelled polyalanines to the presence of two kinds of excimer species: a non-polar excimer (u E =460 nm) of well-defined geometry and a polar excimer emitting at longer wavelengths (u E =520 nm), which may exist in a variety of configurations and where the interchromophoric distance is longer than for the non-polar excimer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation